Structural Differences in Gray Matter between Glider Pilots and Non-Pilots. A Voxel-Based Morphometry Study - Ahamed, Tosif; Kawanabe, Motoaki; Ishii, Shin; Callan, Daniel E. (Frontiers in Neurology, 2014)
Glider flying is a unique skill that requires pilots to control an aircraft at high speeds in three dimensions and amidst frequent full-body rotations. In the present study, we investigated the neural correlates of flying a glider using voxel-based morphometry. The comparison between gray matter densities of 15 glider pilots and a control group of 15 non-pilots exhibited significant gray matter density increases in left ventral premotor cortex, anterior cingulate cortex, and the supplementary eye field. We posit that the identified regions might be associated with cognitive and motor processes related to flying, such as joystick control, visuo-vestibular interaction, and oculomotor control.